PHYTOPLANKTON IN COASTAL WATERS OF DA NANG PROVINCE - Van, Tran Thi Le; Hai, Doan Nhu; Luom, Phan Tan; Anh, Nguyen Thi Mai; Hue, Tran Thi Minh; Duyen, Huynh Thi Ngoc (Vietnam Journal of Marine Science and Technology, 2019)
Phytoplankton, especially community characteristics, in coastal waters of Da Nang have not been well studied. This present study analyzed data of phytoplankton for diversity and abundance from surveys from 2002 to 2016 at 44 stations in the coastal Da Nang waters. A total of 316 taxa from 9 classes were identified: Dinophyceae (134 taxa), Mediophyceae (77 taxa), Coscinodiscophyceae (44 taxa), Bacillariophyceae (36 taxa), Cyanophyceae (3 taxa), Dictyochophyceae (2 taxa), Bacillariophyta classis incertae sedis (1 taxon), Conjugatophyceae (1 taxon) and Thecofilosea (1 taxon). A list of 36 species of potentially harmful microalgae was recorded in coastal waters of Da Nang. In which, Pseudo-nitzschia spp. often had higher cell densities in some locations during the northeast monsoon. Analyzing diversity indices in different locations showed that there were significance differences of Margalef and Shannon indices, low in estuarine area (CS) and higher in the south of Son Tra peninsula (NST). Meanwhile no strong differences of Pielou and Simpson indices were found among the locations. However, there were strong differences of Margalef, Simpson and Pielou indices, which were found over the three studied years (2004, 2005, and 2006), mainly in NST, the northeast of Son Tra peninsula (DBST) and Da Nang bay (VDN). Analysis of species accumulation curves indicated that only 56–95% of species was found compared to maximal expected species richness in all studied locations. DMS analysis showed that there was year-based similarity among the years (ca. 50% of similarity) of phytoplankton communities. Among the studied years, average phytoplankton cell densities in Da Nang bay and the northeast of Son Tra were higher than those in other years and locations. This present study on species richness, expected species richness and variation in phytoplankton abundance suggested that there is a need of increasing sampling efforts, especially in riverine area and DBST for better understanding of characteristics of phytoplankton communities in coastal Da Nang waters